(untitled) (Bangladesh Journal of Urology, 2023)
Introduction: Laparoscopic pyeloplasty (LP) has emerged as a feasible and reliable treatment option for ureteropelvic junction obstruction (UPJO), with a success rate equivalent to that of the classic open procedure. In addition, LP offers benefits associated with minimally invasive techniques, including less pain, shorter hospitalization, and better cosmesis. A variety of modifications have been suggested to ease technical difficulties associated with LP.One suggestion is to use the transmesocolic (TMC) approach. It is an alternative ureteropelvic junction (UPJ) approach that has been shown to reduce operative time compared to the standard laterocolic (LC) approach.It offers a direct path to the left UPJ through the mesocolon with less tissue dissection and bowel manipulation. Materials and Methods: From July 2014 to December 2019 total 35 patients of left side disease have undergone this surgery in our institution. Perioperative results and follow-up data were analysed. Results: Total number of cases 35. Male 21, female 14 among them 27 were child. Operation time 120 minutes to 150 minutes. Hospital stay 2-3 days. Post-operative analgesia with single dose Inj.Pethedine. Antigrade DJ stenting done in all cases. D J stent removed after 4 weeks of surgery. All cases followed up one year. No Per operative & post-operative complication. Conclusion: Direct exposure of the ureteropelvic junction via the mesocolon saves time during the colon mobilization procedure. The approach is safe and feasible even for surgeons with limited experience, and has success rates similar to those of the conventional laterocolic approach. Bangladesh J. Urol. 2023; 26(1): 28-32